Different Impact Of Antiretroviral Drugs On Bone Differentiation In An In Vitro Model. Issue 10 (October 2015) - Esposito, Vincenzo; Perna, Angelica; Lucariello, Angela; Carleo, Maria Aurora; Viglietti, Rosaria; Sangiovanni, Vincenzo; Coppola, Nicola; Guerra, Germano; De Luca, Antonio; Chirianni, Antonio
ABSTRACT Recently increasing emphasis is placed on preventive health and management of chronic comorbidities avoiding long‐term toxicities of antiretroviral therapy (ART). Drawing from this background we decided to use the Saos‐2, osteosarcoma cell line, as a cellular model, to evaluate the effects of some antiretroviral drugs such as abacavir (ABC), tenofovir (TDF), efavirenz (EFV), etravirine (ETR), and darunavir (DRV), on bone differentiation related pathways. According to our observation, treatment with TDF and ABC affects the ability of the cells to produce calcium deposits with a reduced expression of type I collagen gene and p21 mRNA, also increasing the activity of Wnt3a related pathway. On the other hand treatment with EFV and DRV was not related to any significant reduction of calcium deposits but displayed a decrease in the expression of Wnt3a at day 14 and Type I Collagen at day 7 compared with untreated cells, even if this last down regulation was not confirmed at day 14. Instead ETR administration to Saos‐2 cells increases the calcium deposits collagen type I production, as a result of Wnt3a mRNA overexpression, and of an upregulation of collagen type I expression, being also the only drug able to increase the expression of p21 cdk inhibitor as further marker of terminal differentiation. In summary these data suggest the potential negative interference of TDF and ABC on bone differentiation. DRV and EFV partially affect collagen type I production, instead ETR facilitates a positive bone balance as a result of an increased osteoblasts terminal differentiation. J. Cell. Biochem. 116: 2188–2194, 2015. © 2015 Wiley Periodicals, Inc.